Influenza vaccination 2021/22: why is it important?. (1st October 2021) - Duncan, Deborah
Abstract : Each year during the months of September–March we vaccinate against influenza which is caused by the RNA viruses of the family Orthomyxoviridae (influenza viruses) (National Institute for Health and Care Excellence, 2020 ). There are two main types that cause a significant infection – influenza A and influenza B. Influenza A usually causes a more severe illness (Public Health Agency (PHA), 2021 ). Influenza can be a mild self-limiting infection but in some at risk groups it can lead to increased morbidity or mortality. The World Health Organization (2021) recommends which viruses need to be included in influenza vaccines for the northern hemisphere flu seasons. Last year was the biggest NHS influenza vaccination programme ever, with a low incidence of recorded episodes of flu (Public Health England (PHE) et al, 2021a ). This low level of cases of influenza is thought to be due to social-distancing, mask wearing, and increased handwashing (Rubin, 2021 ). The reduction could also be due to the increased influenza vaccination rates, which reached a record high in 2020–2021 (Jones, 2020 ; PHE et al, 2021b ). It is unclear what impact influenza will have this year. Nurses in general practice need to encourage all the preventative measures at their disposal.